Labor Share Heterogeneity and Fiscal Consolidation Programs - Brinca, Pedro (2020)
We show that the labor share of income is an important factor affecting the mechanisms behind fiscal consolidation programs, thus requiring consideration when evaluating fiscal multipliers across countries. We calibrate a life-cycle, overlapping generations model to match key characteristics of different European economies and evaluate the recessive impacts of fiscal consolidation programs. We find a positive relationship between the labor share and the impact fiscal multipliers generated by our model. This result directly follows from the higher weight of labor on production and the lower opportunity cost of leisure present in economies with a higher labor share. Following the impact period, the relationship between the labor share and the fiscal multipliers is dependent on the type of fiscal instrument employed in the consolidation.